Boganmeldelser - Träskman, P. O.; Indahl, Marie; Pösö, Tarja; Laursen, Lau; Klette, Hans; Greve, Vagn; Tamm, Ditlev; Eriksen, Morten; Koch, Ida; Dalberg-Larsen, Jørgen; Munck, Johan; Zila, Josef; et al. (Nordisk Tidsskrift for Kriminalvidenskab, 1995)
Book reviews